(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article analyzes the technologies of cleaning cotton from fine impurities, their mechanical, air-flow and integrated methods from a modern perspective. The study considers the efficiency of cleaning processes, innovations in equipment design, as well as environmental and economic aspects. The article discusses the importance of new technologies in improving the quality of cotton fiber and ways to optimize them. The results of the study can serve to develop sustainable and cost-effective solutions in the cotton industry.